(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: The state and motility of a cosmetic ocular prosthesis are important. Purpose: To develop a novel technique of evisceration or enucleation secondary to trauma, chronic uveitis or uveal melanoma, with permanent and removable fixation of the ocular prosthesis in a musculoskeletal stump (MS). Material and Methods: Group 1 comprised 52 patients with chronic uveitis secondary to trauma and phthisis bulbi who underwent evisceration. After evisceration, a polymer composite implant or a polytetrafluoroethylene (PTFE) implant was used to shape an MS with a hole in it for the pegged prosthesis, and the prosthesis motility in these patients was compared with that in the 13 controls in whom an MS without a hole in it for the pegged prosthesis was shaped. Group 2 comprised 31 patients with uveal melanoma who underwent enucleation with a PTFE implant used to shape an MS with a hole in it. The prosthesis motility in these patients was measured and compared with that in the 100 controls in whom an MS without a hole in it for the pegged prosthesis was shaped. Results: In patients of group 1, total prosthesis motility at 3 and 12 months improved to 132.50 ± 6.40 and 147.30 ± 6.70, respectively, versus 103.70 ± 18.30 and 103.10 ± 6.00, respectively, in the controls. No implant exposure was observed over the follow-up period. In three patients of group 2, diastasis of the conjunctival margins with implant exposure was observed at the margin of the hole at months 3 and 7, which necessitated implant removal. In patients of group 2, total prosthesis motility in the four meridians at 3 and 12 months was 141.60 ± 14.70 and 142.20 ± 16.10, respectively, versus 106.10 ± 13.00 and 103.70 ± 18.30, respectively, in the controls. Conclusion: We found that firm fixation of the pegged ocular prosthesis in the MS allowed improving total prosthesis motility in the four meridians at 3 months and 12 months after evisceration, by 28.8о and 44.2о, respectively, and at 3 months and 12 months after enucleation, by 35.5о and 38.5о, respectively.